Symptoms associated with pregnancy complications along the Thai-Burma border: the role of conflict violence and intimate partner violence. - Falb, Kathryn L; McCormick, Marie C; Hemenway, David; Anfinson, Katherine; Silverman, Jay G (Maternal and child health journal, 2014)
To assess the association between lifetime violence victimization and self-reported symptoms associated with pregnancy complications among women living in refugee camps along the Thai-Burma border. Cross-sectional survey of partnered women aged 15-49 years living in three refugee camps who reported a pregnancy that resulted in a live birth within the past 2 years with complete data (n = 337). Variables included the lifetime prevalence of any violence victimization, conflict victimization, intimate partner violence (IPV) victimization, self-reported symptoms of pregnancy complications, and demographic covariates. Logistic generalized estimating equations, accounting for camp-level clustering, were used to assess the relationships of interest. Approximately one in six women (16.0 %) reported symptoms related to pregnancy complications for their most recent birth within the last 2 years and 15 % experienced violence victimization. In multivariable analyses, any form of lifetime violence victimization was associated with 3.1 times heightened odds of reporting symptoms (95 % CI 1.8-5.2). In the final adjusted model, conflict victimization was associated with a 3.0 increase in odds of symptoms (95 % CI 2.4-3.7). However, lifetime IPV victimization was not associated with symptoms, after accounting for conflict victimization (aOR: 1.8; 95 % CI 0.4-9.0). Conflict victimization was strongly linked with heightened risk of self-reported symptoms associated with pregnancy complications among women in refugee camps along the Thai-Burma border. Future research and programs should consider the long-term impacts of conflict victimization in relation to maternal health to better meet the needs of refugee women.
Keywords: Adolescent; Adult; Crime Victims; Cross-Sectional Studies; Female; Health Surveys; Human Rights Abuses; Humans; Middle Aged; Multivariate Analysis; Myanmar; Pregnancy; Pregnancy Complications; Refugees; Sex Offenses; Sexual Partners; Thailand; Violence; War; Young Adult